The Effect of Microcrack Length in Silicon Cells on the Potential Induced Degradation Behavior - Xianfang Gou; Xiaoyan Li; Shaoliang Wang; Hao Zhuang; Xixi Huang; Likai Jiang (International Journal of Photoenergy)
The presence of microcracks may lead to loss in the module output power and safety hazard of the module. This paper investigated whether the existed microscopic microcracks in cells will facilitate the PID behavior. Cells with different degrees of microcracks were fabricated into small modules to undergo the simulated PID test. The I-V performance and EL images of the modules were characterized before and after the PID test. The obtained results demonstrate that with the increase in the microcracked area or length, the modules would show a more serious PID behavior. The mechanism of this microcrack length-related degradation under high negative bias was proposed.